Pengaruh Expanded Marketing Terhadap Minat Berkunjung Di Museum Asi Mbojo - Yogi Arief Wijaksono; Muhajirin Muhajirin (Tirtayasa Ekonomika, 2020)
Tourism has now become a global need. The development of increasingly rapid globalization is very influential on the development of industry, including the tourism industry. Currently the tourism industry is part of one of the central foreign exchange earners for developing countries including Indonesia. The aim to be achieved is to increase expanded marketing of visiting interest in the Asi Mbojo museum. The data used is primary data. The research sample of 70 visitors who visited the ASI MBOJO museum. Data analysis tool in this research uses simple linear regression. The results of this study indicate that expanded marketing influences the interest in visiting the museum Asi Mbojo.